Intercept Probability Analysis of the Energy Harvesting Enabled Multisource Half-Duplex Relaying Network with Receiver Diversity Techniques - Tan N. Nguyen,; Pham Ngoc Son,; Lam-Thanh Tu, (Journal of Technical Education Science, 2024)
In this paper, the performance of a multisource half-duplex relaying network utilizing the time-switching approach is investigated. Particularly, the relay simply relies on the harvested energy from the selected source to perform its operations such as amplifying and forwarding the source signals. The selected source is chosen according to the channel gain of the legitimate link from all source nodes to the relay. Under this context, the intercept probability (IP) of the considered system model with both maximal ratio combining (MRC) and selection combining (SC) is analyzed and presented in the integral-form and closed-form expressions. Monte Carlo simulations are deployed to confirm the accuracy of the analytical framework as well as to find out the impact of the main system parameters. The outcomes indicate that the simulation and analytical values are the same in all cases. It also unveils that the MRC is always superior to the SC scheme. Additionally, the IP is a concave function with respect to the time-switching ratio while the IP is a monotonic function regarding the number of source nodes, transmit power, etc.